2022
DOI: 10.34119/bjhrv5n1-237
|View full text |Cite
|
Sign up to set email alerts
|

Compreendendo o adoecimento mental pelo esgotamento profissional da Síndrome de Burnout: uma revisão integrativa / Understanding Burnout Syndrome mental illness: an integrative review

Abstract: RESUMOA Revisão Integrativa justifica-se quando se quer conhecer um assunto com mais clareza. Nesse caso, justifica-se ainda, social e politicamente pela necessidade de aclarar a reflexão sobre a compreensão do adoecimento pela síndrome de burnout em diversos tipos de trabalhadores, tendo em vista seus diversos espaços e atuações laborais. O modelo que foi utilizado nesse estudo teve como base as diretrizes dos Principais Itens Para Relatar Revisões Sistemáticas e Meta-análises (PRISMA), com busca nas bases de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
0
2
0
5
Order By: Relevance
“…Tal exposição pode estar associada a déficits e atrasos na linguagem, comunicação, habilidades motoras e saúde socioemocional. Nesse sentido, é crucial que as crianças utilizem as telas de forma supervisionada e adequada, com limitação do tempo de exposição (ROCHA et al, 2022).…”
Section: Editora Pascalunclassified
See 2 more Smart Citations
“…Tal exposição pode estar associada a déficits e atrasos na linguagem, comunicação, habilidades motoras e saúde socioemocional. Nesse sentido, é crucial que as crianças utilizem as telas de forma supervisionada e adequada, com limitação do tempo de exposição (ROCHA et al, 2022).…”
Section: Editora Pascalunclassified
“…Embora existam alguns benefícios na utilização de tecnologias interativas de alta qualidade, como a aprendizagem, o uso excessivo de telas pode trazer efeitos adversos. Entre eles, o sedentarismo, a obesidade, as doenças metabólicas e cardiovasculares, a redução do tempo de interação social, a desregulação do sono e a exposição a conteúdos inadequados para a faixa etária são fatores de risco associados ao uso prolongado de telas (ROCHA et al, 2022).…”
Section: Editora Pascalunclassified
See 1 more Smart Citation
“…These stressors, if persistent, can lead to Burnout Syndrome (BS). [1] The first research on BS is the result of studies on emotions and ways of dealing with them, developed with professionals who, due to the nature of their work, needed to maintain direct contact with other people. [2] BS is directly related to the decrease in quality of life, it can be observed that the international scientific literature shows many controversies about the concept and the term "quality of life", from synonyms such as "health conditions" and "social functioning" ", even about its own definition.…”
Section: Introductionmentioning
confidence: 99%
“…It can be easily observed when individual expectations related to professional practice are revealed through a non-corresponding reality, giving rise to a feeling of failure and impotence. [1] The syndrome has a high prevalence in professionals in direct contact with people and exposed to an overload of work, presenting greater depletion of energy, lack of professional fulfillment, emotional exhaustion, depersonalization and reduced professional fulfillment or a feeling of incompetence. [1] The implementation of Quality of Life at Work occurs when the work unit and the people involved in it as a whole are looked at, what he calls the biopsychosocial approach, which represents the differential factor for carrying out diagnoses, campaigns, creating services and implementation of projects aimed at the preservation and development of people while working at the company.…”
Section: Introductionmentioning
confidence: 99%